A new aero-structural optimization method for wind turbine blades used in low wind speed areas. (1st January 2019) - Yang, Han; Chen, Jin; Pang, Xiaoping; Chen, Gang
Abstract: The wind turbine blades used in lower quality wind resources have been recently designed. The designed blades for low wind speed areas are scaled version of blades used in high wind speed sites with longer blade lengths, same chord length and same airfoils series. A discrete optimization method for wind turbine blade used in low wind speed sites is proposed. In the optimization process, both aerodynamic and structural parameters are considered as design variables. The airfoil design is also considered in the optimization process to improve the aerodynamic and structural performance by the method of airfoil integrated theory. The Blade Element Momentum theory is used to evaluate the blade aerodynamic performance and the Classical Laminate Theory is used to estimate the stiffness and mass per unit of each blade section. Finally, a Finite Element Method structural analysis is used to verify the strength under the extreme loading conditions. To prove the efficiency and robustness of the design, a commercial 2.1 megawatt HAWT blade is used as a case study. The results show that the aerodynamic and structural performance of the new blade is improved compared with that of the original one.